Subtypes-specific patterns in HIV type 1reverse transcriptase and protease in Oyo state, Nigeria: implications for drug resistance and Host Response (2006)
As the use of antiretroviral therapy becomes more widespread across Africa, it is imperative to characterize baseline molecular variability and subtype-specific peculiarities of drug targets in non-subtype B HIV-1 infection. We sequenced and analyzed 35 reverse transcriptase (RT) and 43 protease (PR) sequences from 50 therapy-naive HIV-1-infected Nigerians. Phylogenetic analyses of RT revealed that the predominant viruses were CRF02_AG (57%), subtype G (26%), and CRF06_cpx (11%). Six of 35 (17%) individuals harbored primary mutations for RT inhibitors, including M41L, V118I, Y188H, P236L, and Y318F, and curiously three of the six were infected with CRF06_cpx. Therefore, CRF06_cpx drug-naive individuals had significantly more drug resistance mutations than the other subtypes (p = 0.011). By combining data on quasisynonymous codon bias with the influence of the differential genetic cost of mutations, we were able to predict some mutations, which are likely to predominate by subtype, under drug pressure. Some subtype-specific polymorphisms occurred within epitopes for HLA B7 and B35 in the RT, and HLA A2 and A*6802 in PR, at positions implicated in immune evasion. Balanced polymorphism was also observed at predicted serine-threonine phosphorylation sites in the RT of subtype G viruses. The subtype-specific codon usage and polymorphisms observed suggest the involvement of differential pathways for drug resistance and host-driven viral evolution in HIV-1 CRF02_AG, subtype G, and CRF06_cpx, compared to subtype B. Subtype-specific responses to HIV therapy may have significant consequences for efforts to provide effective therapy to the populations infected with these HIV-1 subtypes